Metabolic bariatric surgery and combined multilevel surgery as a treatment for obstructive sleep apnea patient with obesity - Bienia, Grzegorz; Świętochowski, Jakub; Żołnierek, Maja; Siekierko, Nikola; Lubczyńska, Zuzanna; Lewandowski, Mateusz; Kotusiewicz, Wiktoria; Popravko, Yevheniia; Kostrzewa, Aleksander (Journal of Education, Health and Sport, 2023)
Body mass index (BMI) and the degree of obstructive sleep apnea (OSA) are strongly correlated. Managing obesity is an important strategy for preventing and treating OSA. Bariatric surgery can lead to significant weight loss and improvements in metabolic function, which can have beneficial effects on OSA symptoms within obese population. There is a relative lack of data directly comparing the different types of bariatric surgery and multilevel upper airway surgery for the treatment of obstructive sleep apnea (OSA). While there is some evidence to suggest that bariatric surgery can improve OSA symptoms in obese individuals, and multilevel upper airway surgery can improve OSA symptoms in some cases of anatomical obstruction, there is limited research directly comparing these treatment options. Therefore, this review provides an update on the relationship between OSA, MBS and MLS for demonstrating the significance of multidisciplinary surgery approach for obese patients with OSA.